Analisis Pelaksanaan Posyandu Balita di Wilayah Kerja Puskesmas Kayu Jao Kabupaten Solok dengan Model CIPP (Context, Input, Process, and Product) - linggana Radita; Chriswardani Suryawati; Rani Tiyas Budiyanti (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
Background: Puskesmas Kayu Jao is still experiencing nutritional problems with a prevalence of stunting of 14.6%. The existence of posyandu can prevent and overcome child nutrition problems, but the implementation of posyandu in the working area of Puskesmas Kayu Jao is not optimal, which is characterized by low coverage of weighing toddlers and not reaching the 80% target. This study aims to analyze the implementation of posyandu for toddlers through the CIPP (Context, Input, Process, Product) approach; Methods: This research is a qualitative research with a descriptive approach through in-depth interviews, conducted in June-July 2024. The research subjects were determined using a purposive technique. The main informants included posyandu cadres, human development cadres, and the head of the village service section. Triangulation informants included nutrition officers from the Kayu Jao Health Center, midwives and parents of toddlers; Results: In the context aspect, it is important to increase the understanding of parents of toddlers regarding the purpose of posyandu as a follow-up to existing problems. In the input aspect, in the implementation of activities there are no SOPs and the skills of cadres are lacking as well as the availability of infrastructure and funding is inadequate. In the process aspect, there is a cadre organizational structure, during the implementation of posyandu, there is a lack of support from community leaders, and the implementation is not optimal at table three filling KMS and table four health counseling services. In the product aspect, it was found that the achievement of SKDN, only the achievement of K/S met the trajectory and other indicators were still low, not reaching the performance target of the nutrition program in 2023; Conclusions: The process of implementing is not in accordance with the guidelines for organizing posyandu by the Indonesian Ministry of Health and SKDN coverage does not reach the target. Organizing related training related to communication strategies and providing IEC media to assist in providing education and increasing support from community leaders during the implementation of posyandu toddlers.